PRISMA Systematic Review of the Use of Social Networks as Educational Tools in the Field of Visual Culture from a Social Psychology Perspective - Santos Velandia, Juan Carlos; Elvira Zorzo, María Natividad (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This PRISMA-based systematic review explores the integration of social networks as educational tools in teaching visual culture. Publications from 2010 to 2023 were analyzed, using databases like Scopus and Google Scholar. Of 150 articles reviewed, 25 met the inclusion criteria. The results show that social networks enhance access to visual resources, foster collaboration and student engagement, and enable real-time interactions through mobile devices. The study emphasizes the necessity of teacher training and effective online time management to maximize the educational potential of these platforms.